The Importance and Interaction Indices of Bi-Capacities Based on Ternary-Element Sets - Baghdad Science Journal (مجلة بغداد للعلوم)
Grabisch and Labreuche have recently proposed a generalization of capacities, called the bi-capacities. Recently, a new approach for studying bi-capacities through introducing a notion of ternary-element sets proposed by the author. In this paper, we propose many results such as bipolar Mobius transform, importance index, and interaction index of bi-capacities based on our approach.